Conversational Maxims in Constitutional Court - Khodijah, Siti (Journal of Language Intelligence and Culture, 2019)
This paper discussed conversational Maxims in Constituional Court that related to the general election 2019 in Indonesia. However, this reseach focused on the flouted maxims that is used by the witness in constitutional court in answering the judge’s questions. In this paper, the writer choose the utterances that is produced by the witness in constitutional court, since there are many maxims that are flouted by the witness in giving his answer. In analyzing this conversation, the writer used Grice’s theory which established four maxims, they are maxims of quantity, maxims of quality, maxims of relevance, and amxims of manner. In addition, this research used descriptive qualitative approach. Since, the data are in the form of sentences. The analysis revelas some findings. It’s found that mostly the witness flouted the maxims of relevance.